Signal-To-Noise Ratio Estimations In Wireless Communications - Lenin, G (2005)
In this thesis, three SNR estimation techniques are compared and evaluated, Square of the Mean by the Variance (SMV), Square-Law Moments and Maximum Likelihood estimators, on AWGN channel. The performance measures are mean square error (MSE) and bias. The maximum Likelihood estimator has the best overall performance.